2006
DOI: 10.1111/j.1399-302x.2006.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Helicobacter pylori in the oral cavity of 10 non‐dyspeptic subjects demonstrated by real‐time polymerase chain reaction

Abstract: Helicobacter pylori is a gram-negative, curved, microaerophilic organism that has been implicated in the aetiology of gastritis, in the process of gastric and duodenal ulcer formation, and in gastric cancer (15,17). Approximately 10% of individuals are affected by gastritis and/or gastric ulcer during their lifetime and over 50% of the world's population carries this infection (7). The prevalence of gastric H. pylori infection depends on age and varies strongly between developing and developed countries, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 30 publications
3
25
1
Order By: Relevance
“…Also they did not find any association between H.pylori in dental plaque and stomach which is not in agreement with our study. Martinez-Gomis et al (15) found no H. pylori in the dental plaque of non-gastritis patients that supports our findings. Gebara et al (16) (20).…”
Section: Discussionsupporting
confidence: 82%
“…Also they did not find any association between H.pylori in dental plaque and stomach which is not in agreement with our study. Martinez-Gomis et al (15) found no H. pylori in the dental plaque of non-gastritis patients that supports our findings. Gebara et al (16) (20).…”
Section: Discussionsupporting
confidence: 82%
“…In studies in which H.pylori was detected in dental biofilm and saliva with RT-PCR, Burgers et al [3], Altındiş et al [55], Sayed et al [69] and Martinez-Gomis et al [70] used adults as the subjects, Bharath et al [71] completed their studies using with adults and children. Investigations conducted by, Valdez-Gonzales et al [5] and Ou et al [72] involved the use of only children.…”
Section: Discussionmentioning
confidence: 99%
“…However based on some evidence oral cavity can be considered a reservoir for H. pylori in non-dyspeptic individuals, some researchers believe in temporary presence of H. pylori in such situation (Martinez-Gomis et al, 2006;Burgers et al, 2008). Other researchers believe that non-infectious H. pylori might exist in the oral cavity which is just able to form colonies and invade tissues under special conditions such as concomitant infections (Martinez-Gomis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers believe that non-infectious H. pylori might exist in the oral cavity which is just able to form colonies and invade tissues under special conditions such as concomitant infections (Martinez-Gomis et al, 2006). H. pylori colonization might be necessary for the induction of OLP but not crucially detectable in the generated OLP lesions by PCR or bacterial culture (Riggio et al, 2000;Shimoyama et al, 2000).…”
Section: Discussionmentioning
confidence: 99%